2012
DOI: 10.1016/j.amepre.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Successful Weight Loss Among Obese U.S. Adults

Abstract: Background Little is known about weight control strategies associated with successful weight loss among obese U.S. adults in the general population. Purpose To identify strategies associated with losing at least 5% and 10% of body weight. Methods Multivariable analysis of data from obese adult (BMI ≥30) participants in the 2001–2006 NHANES to identify strategies associated with losing ≥5% and ≥10% of body weight (conducted in 2009–2011). Results Of 4034 obese adults, 2523 (63%) reported trying to lose we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(112 citation statements)
references
References 23 publications
4
101
0
7
Order By: Relevance
“…Apesar de terem sido adoptadas por uma pequena proporção de homens e mulheres, o que é consistente com outros estudos epidemiológicos, 11,19,29,30 devem ser alvo de atenção por parte das entidades promotoras de saúde pois este tipo de estratégias tem sido associado a comportamentos de sobrealimentação, compulsão alimentar e a insucesso no que respeita ao controlo do peso. [31][32][33] Observaram-se diferenças específicas por sexo no que respeita à adopção de algumas estratégias para controlar o peso. Em contraste com outros estudos 11,20,30 em que a mesma proporção de homens e mulheres reportou praticar atividade física para tentar perder peso, em Portugal a prática de a atividade física é mais prevalente nos homens a tentar gerir o peso.…”
Section: Discussionunclassified
“…Apesar de terem sido adoptadas por uma pequena proporção de homens e mulheres, o que é consistente com outros estudos epidemiológicos, 11,19,29,30 devem ser alvo de atenção por parte das entidades promotoras de saúde pois este tipo de estratégias tem sido associado a comportamentos de sobrealimentação, compulsão alimentar e a insucesso no que respeita ao controlo do peso. [31][32][33] Observaram-se diferenças específicas por sexo no que respeita à adopção de algumas estratégias para controlar o peso. Em contraste com outros estudos 11,20,30 em que a mesma proporção de homens e mulheres reportou praticar atividade física para tentar perder peso, em Portugal a prática de a atividade física é mais prevalente nos homens a tentar gerir o peso.…”
Section: Discussionunclassified
“…It was not possible to evaluate intentionality of weight loss. Previous studies have reported that the majority of obese individuals would like to lose weight and a large proportion are actively attempting to reduce their weight, 115,116 so a relatively high level of intentionality among obese participants may be assumed. Additionally, monitoring of BMI among obese patients in primary care has been shown to positively predict treatment.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The MOVE! program is estimated to be initiated by approximately 10 % of eligible patients, which reflects higher participation in weight loss programs than is reported in the general population [8]. However, it is apparent that the vast majority (about 90 %) of veterans who are eligible are not participating.…”
Section: Introductionmentioning
confidence: 99%
“…Attrition from weight loss treatments has been the focus of considerable research attention [7], whereas less attention has been given to the first step in utilization: initiating treatment. Many patients with obesity are not seeking weight loss, and many of those who are trying to lose weight are not initiating empirically supported treatments in the first place [8,9]. Of additional concern, certain populations may be less likely to use available treatments.…”
Section: Introductionmentioning
confidence: 99%